STUDY OF THE CAUSES OF DIVORCE IN THE MUSLIM COMMUNITY OF KAMPA DISTRICT, KAMPAR REGENCY, IN 2021 REVIEWED BASED ON ISLAMIC LAW - Afandi, Muhammad Haikel (Universitas Islam Negeri Sumatera Utara Medan, 2023)
The background of this study is that marriage is the union of two individuals, a man and a women, to form a harmonious household, and it is human nature to pair up with one another. However, the phenomenon in the field suggests other wise, as evidenced by the high number of domestic disputes, even leading to divorce. Kampa subdistrict is one of the subdistricts in Kampar Regency where nine cases of divorce by repudiation were recorded in 2021. This phenomenon of divorce by repudiation needs to be explored in more detail, condisering that the people of Kampa are religious and traditional. The purpose of this study is to describe the causes of divorce in Kampa Subdistrict and the meaning of divorce for those who in Kampa Subdistrict. This study is field research that focuses on the causes of divorce among the Muslim population of Kampa Subdistrict, Kampar Regency, in 2021, based on Islamic Law. In this study, the author used descriptive analytical analysis, which is what respondents stated in writing or verbally, as well as their actual behavior, which was researched and studied as a whole. The results of this thesis research are the causes of divorce in Kampa District, Kampar Regency, as follows: economic factors, infidelity, domestic violence and education. Meanwhile, there are two meanings of divorce for theme, as follows: freedom and a way out of problems.